Al-water reactivity of AlMgGaInSn alloys used for hydraulic fracturing tools. (12th April 2018) - Du, B.D.; He, T.T.; Liu, G.L.; Chen, W.; Wang, Y.M.; Wang, W.; Chen, D.M.
Abstract: In order to develop a new kind of dissolvable alloy used for hydraulic fracturing tools, a series of AlMgGaInSn alloys with different Mg contents were prepared by smelting and casting methods to investigate the effect of Mg on the reactivity of alloys with water. Their microstructures were investigated by means of XRD and SEM. The Volta potential difference (ΔVPD) of the interfacial phases with Al was measured using AFM/SKPFM. Mg forms different intermetallic compounds with low melting point metals, depending on Mg additions in alloys. Different from the formation of In3 Sn phase in AlGaInSn alloys, the In3 Sn phase disappears in Mg-bearing alloys. The experiments found that the reactivities of Mg-bearing alloys with water are closely related to Mg content of alloys and water temperature. The alloys react with water slowly at the beginning of reaction, following with a fast reaction. From the corrosive morphologies of alloys, the precipitation of low melting point metals from interfacial phases was observed at Al grain boundaries. The lower electric potential of interfacial phases than Al was accounted for the precipitation of low melting point metals, because the interfacial phases form micro-galvanic cells with Al when alloys contact with water. A reaction mechanism of Mg-bearing alloys with water was proposed to explain the reactivties of alloys with water. Highlights: The intermetallic compounds containing low melting point metals form micro-galvanic cells with Al. The low melting point metals precipitated at Al grain boundaries lead to continuous Al-water reaction. The Mg content and water temperature control the reactivity of AlMgGaInSn alloys with water. The AlMgGaInSn alloys can be used as dissolvable fracturing tools in hydraulic fracturing.